Gestión del software fénix para la administración de los inventarios en la Empresa Detodo.Com en la ciudad de Babahoyo. - Ruiz Guillen, Holger Fabricio (2022)
The objective of this technological proposal is to automate the inventory and administrative activities of the company Detodo.com located in the city of Babahoyo, in which it has a high number of clients, unfortunately the current process is handled in a manual which allows the information to become tedious. This technological proposal presents two such modules: administrative and web portal. The first will allow to solve the loss and disorder of the information through transactional screens that allow to have a control in the registry of clients, invoicing and consultations, the second is to present information and register the inventories and invoicing in said fénix portal, in this way prevent a customer or merchandise from being left out of the process. The proposal will be used by those who make up the company and thus the processes are clear and concise. Finally, it will be possible to automate and optimize the billing or registration time of a client, avoiding the data, since it is a common problem when filling out information manually and in files.